Pengaruh Pelatihan Dan Pengembangan Sumber Daya Manusia Terhadap Kinerja Pegawai Pada Dinas Sosial Kota Bima - Karlina, Leni; Badar, Muhammad; Irawan, Ikba (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
This study aims to analyze the effect of training and human resource development on employee performance at the Social Service Office of Bima City. The research was motivated by the low level of employee productivity, limited budget allocation for development programs, and the tendency of some employees to delay task completion. The study employs a quantitative approach with an associative method. The population consists of 59 employees, with a sample of 35 civil servants selected through purposive sampling. Data were collected using questionnaires, observation, interviews, and documentation. The analysis techniques include validity and reliability tests, classical assumption tests, multiple linear regression, t-test, and F-test. The findings show that both training and human resource development have a significant and positive impact on employee performance. Training improves employee skills, while development efforts enhance competencies to meet organizational demands. The study suggests that structured training and development programs should be optimized to improve public service performance.